Navigating mental health in space: gut–brain axis and microbiome dynamics - Jiseon Yang; Hee-Dae Kim; Jennifer Barrila; Se-Hui Lee; Cheryl A. Nickerson; C. Mark Ott; Sharon A. Israel; Alexander Choukér; Jin-Young Yang (Experimental and Molecular Medicine)
Abstract Long-term space travel presents significant mental health challenges, with documented psychological and neurological impacts observed during spaceflight and in simulated space environments. Terrestrial studies have highlighted the connection between the human gut microbiome and neuropsychological health, known as the gut–brain axis. Recent research has demonstrated alterations in astronauts’ microbiomes during spaceflight. Here we explore interesting parallels between these microbiome changes in astronauts and those observed in terrestrial studies involving individuals experiencing psychological distress. Key areas of focus include how various space-related stressors impact the complex interplay between the gut microbiome, immune responses and mental health outcomes. This is illustrated by the effects of space radiation and circadian rhythm disruptions on the microbiome, as well as the roles of immune regulation and the integrity of gut and blood–brain barriers in shaping mental health outcomes through the gut–brain axis. Potential interventions and strategies for microbiome monitoring are suggested as critical to mitigating psychological risks during extended space missions. These findings underscore the need for further research to better understand how the microbiome responds to spaceflight environments and to develop targeted interventions that safeguard mental health during long-duration missions.